Reachout edu / Sharifah Muzlia Syed Mustafa, Nurul Fitriah Alias and Lina Mursyidah Hamzah - Syed Mustafa, Sharifah Muzlia; Alias, Nurul Fitriah; Hamzah, Lina Mursyidah (2020)
The Covid-19 pandemic leading to restricted movement control has seen the educational institutions quickly adopting the online-distance learning approach. Students and academicians must adopt the skills of conducting classes online. After a semester of noting the challenges that students came across with ODL and confirming the need from students' need-assessment survey, the counselling lecturers have come up with a method to help students in distress. Thus, the creation of the counselling blog is an initiative taken by the counselling lecturers to provide students with a venue to read about self-help tips and information about counselling. The blog has several headings that students can delve into if they want to search more on briefs about counselling, activities, websites, and contacts of professional helps. There is also a venue for chatting online with a lecturer on duty, and students can write in anonymously to share their life experiences. Early response from students showed encouraging and positive response where they applauded the attractive designs and contents of the blog. It is recommended that such step is taken by other educational institutions in the effort of assisting students at the faculty level before they are referred to professional help, if in need.